The effectiveness of rebozo and pelvic rocking in reduction intensity of labor pain during 1 active phase - Fajriah, Asruria Sani; Khorinisa, Depi; Retnaningtyas, Erma; Siwi, Retno Palupi Yonni; Widiyanto, Aris (Universitas Jenderal Achmad Yani Yogyakarta, 2024)
Background: Pain during labor is common process that involves the mother's physiology and psychology. Non-pharmacological management of labor pain includes the rebozo technique and pelvic rocking. Objective: To determine the effectiveness of the rebozo and pelvic rocking techniques on the intensity of labor pain during the first active phase.Methods: Pre-experimental research design using 2 groups pre and post test group design. The sawas 32 people and samples were taken using total sampling. The independent variable is the rebozo and pelvic rocking technique, the dependent variable is the intensity of labor pain during the 1st active phase. Data analysis used the Wilcoxon signed rank test.Results: 81.3% of respondents who were given pelvic rocking therapy experienced a reduction in pain from severe pain to moderate pain and the rest to mild pain. There is an influence of the rebozo technique and pelvic rocking on the intensity of pain in the first stage of labor where the P value is (0.000 < 0.05). Conclusion: Rebozo is a long piece of cloth that is used to help couples feel comfortable during the birth process with techniques that can be learned together with your partner